2016
DOI: 10.1080/19648189.2016.1182084
|View full text |Cite
|
Sign up to set email alerts
|

Oil palm shell as an agricultural solid waste in artificial lightweight aggregate concrete

Abstract: The aim of this study was to produce a sustainable construction material by incorporating an agricultural solid waste, namely oil palm shell (OPS), in an artificial lightweight aggregate concrete. For this purpose, in a structural lightweight aggregate concrete made of expanded clay, the lightweight aggregate was substituted with OPS in 0, 25 and 50% by volume. Properties such as compressive strength under different curing conditions, as well as density, splitting tensile and flexural strengths, modulus of ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…It can be highlighted that the decline in density was noticed for OPS lightweight concrete, extending from 11% to 23% of the NCA concrete. Shafigh et al [42] observed this consistent phenomenon of test results for palm shell LWC, where the density was approximately 14-19% lighter than NCA concrete. The decrease in the density of palm shell aggregate lightweight concrete is observed due to the more permeable characteristics of the palm shell that is stuck to the aggregates.…”
Section: Properties Of Fresh Concretesupporting
confidence: 54%
See 1 more Smart Citation
“…It can be highlighted that the decline in density was noticed for OPS lightweight concrete, extending from 11% to 23% of the NCA concrete. Shafigh et al [42] observed this consistent phenomenon of test results for palm shell LWC, where the density was approximately 14-19% lighter than NCA concrete. The decrease in the density of palm shell aggregate lightweight concrete is observed due to the more permeable characteristics of the palm shell that is stuck to the aggregates.…”
Section: Properties Of Fresh Concretesupporting
confidence: 54%
“…It seems to minimize the dead load of the RC members, which satisfied the LWC requirement according to ASTM C330/C330M-17a [18]. Other researchers also reported a similar finding in their experimental investigation on structural lightweight concrete production with expanded clay [42]. However, LWC is considered with a density below 2160 kg/m 3 based on a practical application [43].…”
Section: Properties Of Fresh Concretementioning
confidence: 62%
“…Their load-carrying behaviors for structural uses are defined by the requirements of codes of practice. In the variety of available concrete material technologies, lightweight concretes, which include foamed concrete [3][4][5], oil palm shell concrete [6,7], and lightweight aggregate concrete [8,9], offer alternative options for building materials by achieving the constraint of structural use. For this, ACI design specification has identified a minimum compressive strength of 17 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Xerogel is microporous and can be defined as a low-density biomaterial employed for various promising applications in different fields [9]. Xerogel is produced from gels by replacing a liquid phase, commonly solvent crystals, with a gaseous phase with no ruin of the created porous solid architecture [10,11,12]. The significance of Xerogel-based PKS is that it will become an effective and low-cost material widely used globally as an absorbent, not only effective on toxic gases but also in absorbing engine oil and heavy metal removal in wastewater.…”
Section: Introductionmentioning
confidence: 99%